2017
DOI: 10.1371/journal.pone.0181602
|View full text |Cite
|
Sign up to set email alerts
|

Retention and recruitment of general dentists in an adjunct teaching model—A pilot study

Abstract: Purpose/ObjectivesRetention and recruitment of part time clinical adjunct faculty members in dental education is becoming increasingly difficult as dental schools come to rely on this workforce for their increased involvement in clinical education. Contributing factors include full time faculty shortage, aging workforce, practice and student debt, practice and family commitments, and financial compensation. This study attempts to ascertain barriers to teaching so appropriate strategies can be formulated to add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 14 publications
(16 reference statements)
3
14
0
Order By: Relevance
“…In the current study, 56% of the participants indicated that they received remuneration of more than $400 per day which is similar to the 54% reported by Howe et al . Only 26% of dentist PPFs, compared to all dental therapist and dental hygienist PPFs, indicated that they were paid less than $400 per day.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In the current study, 56% of the participants indicated that they received remuneration of more than $400 per day which is similar to the 54% reported by Howe et al . Only 26% of dentist PPFs, compared to all dental therapist and dental hygienist PPFs, indicated that they were paid less than $400 per day.…”
Section: Discussionsupporting
confidence: 85%
“…The main reason given for reduced interest in clinical teaching in the current study was lack of support and encouragement from the The school could provide more support to increase the opportunities for PPFs to study postgraduation or to involve them in academic In the current study, 56% of the participants indicated that they received remuneration of more than $400 per day which is similar to the 54% reported by Howe et al 9 Only 26% of dentist…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations